If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4000(0.20 + -1x) = x (0.20 * 4000 + -1x * 4000) = x (800 + -4000x) = x Solving 800 + -4000x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 800 + -4000x + -1x = x + -1x Combine like terms: -4000x + -1x = -4001x 800 + -4001x = x + -1x Combine like terms: x + -1x = 0 800 + -4001x = 0 Add '-800' to each side of the equation. 800 + -800 + -4001x = 0 + -800 Combine like terms: 800 + -800 = 0 0 + -4001x = 0 + -800 -4001x = 0 + -800 Combine like terms: 0 + -800 = -800 -4001x = -800 Divide each side by '-4001'. x = 0.1999500125 Simplifying x = 0.1999500125
| -7(z+6)=-70 | | 4-5x=-59 | | 6(5)-10y=10 | | 43-7x= | | .79saw=24 | | 5x+7-4x=15 | | 5xsquared-20=0 | | 4x+y-3=0 | | u^2-u-8=0 | | 11-8x=2(8-4x)-5 | | 32=25-7x | | (22B-9)-7(3B+1)=-4 | | 30-10y=10 | | 4/(1-((5-25x)/4)) | | 68=m-46 | | x+7overx-5=0 | | f(x)=-x^2+1.8x+14.4 | | 2(4-x)=x | | -2x-4x-12=6 | | 3j+-2j-11=7 | | -8x+2y=-6 | | -x-2x-7x-2=32 | | n^2+12n-49=-10 | | 5(2+x)=7x-20 | | (15x-9)=y | | 2x(2-x)=x | | 9n-32=24n-1 | | 0.32/0.56=8/x | | 8-8b=8(b-7) | | N+4-3=2 | | f(x)=-2x^2+4x-1 | | -4(5t-4)+7t=5t-7 |